SOLID WASTE AND ITS IMPACT ON THE ENVIRONMENT IN OMDURMAN - Amir Hassan Abdullah Muhammed (Universitas Negeri Semarang, 2018)
The research dealt with solid waste and its impact on the environment in Omdurman locality and it is considered a modern and contemporary subject. The aim of the research is to identify the methods related to waste, environmental pollution and to try to search for qualitative and planning criteria for the definition of solid waste in Omdurman. The researcher used several approaches to suit the nature of the research, including the historical approach to tracking the solid waste stages in Omdurman. The descriptive approach was used to describe the natural and human phenomena, as well as the analytical statistical approach (spss) to collect, arrange, analyze and interpret the data.With waste in general and solid waste in particular. The research has reached a number of results, the most important of which is: The increasing population growth has a direct relationship to increase the quantity of waste. The absence of awareness and environmental culture in the population led to the aggravation of this problem, resulted in the accumulation of waste, and spreadin the streets, fields and tents throughout the study area. The absence of a private sector capable of contributing to the service of waste, where all experiences with the private sector proved their failure to achieve real support for cleaning bodies. Poor planning in the infrastructure of roads inside and outside the local.